Boosting Alkaline Hydrogen Evolution on Stoichiometric Molybdenum Carbonitride via an Interstitial Vacancy‐Elimination Strategy. Issue 25 (27th May 2022) - Dai, Liming; Yao, Fanglei; Yu, Lei; Fang, Chenchen; Li, Jing; Xue, Liang; Zhang, Shengli; Xiong, Pan; Fu, Yongsheng; Sun, Jingwen; Zhu, Junwu
Abstract: An interstitial vacancy on molybdenum nitride has been determined as a negative factor towards the alkaline hydrogen evolution reaction (HER) by reason of upraising the d orbitals of Mo. Nevertheless, investigations aiming to eliminate the vacancies are rarely reported. Here, an interstitial reconfiguration method for the design of stoichiometric molybdenum carbonitride (Mo2 CN) is proposed, in which the vacancies are fulfilled by lattice carbon. Multiple fine structural analyses alongside with the theoretical calculations indicate that beyond lower the d orbitals of Mo by the hybridization of additive p‐d orbitals, lattice carbon also behaves as the extra active center with exceptional H adsorption/desorption energy. Mo2 CN reveals an adorable overpotential of − 84 mV at a current density of 10 mA cm −2 with a long‐term electrochemical stability by accompanying the nitrogen‐doped carbon substrate. It is anticipated that the vacancy‐eliminating concept will provide a constructive entry point for the rational design of electro‐catalysts and beyond. Abstract : An interstitial vacancy‐elimination strategy has been proposed and utilized to fabricate the stoichiometric molybdenum carbonitride with striking alkaline hydrogen evolution reaction performance. Beyond modulating the d orbitals of Mo atoms to the maximum extent, lattice carbon atoms also behave as the extra active centers with exceptional H adsorption/desorption energy, effectively releasing the trapped H in original vacancy sites.